PERSEPSI PEMANFAAT TERHADAP KINERJA LEMBAGA UED-SP AL-RIZKI DI DESA KAMPUNG PULAU KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Acriski '; Susy Edwina; Shorea Khaswarina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Economic Business Village Save-Loans (UED-SP) according to Regulation No.06 of 1998 is an institution that is engaged in the savings and loan and belong to village community / urban village are cultivated and managed by village communities / urban village. The purpose of this study to determine: (1) institutional effectiveness as perceived by users of UED-SP. (2) Efficient use of resources is based on the perception of users UED-SP. (3) Sustainability institution based on the perception of users UED-SP. The sample in this study the beneficiary of funds UED-SP In the Kampung Pulau Village SubdistrictRengatIndragiri Hulu Regencyamounting to 34 people with the selection of Simple Random Sampling. Analysis of the performance institutions UED-SP was measured using a Likert's Summated Rating Scale (LSRS). Institutions Performance UED-SP based on the perceptionusers belonging to